2020
DOI: 10.1038/s41467-020-18418-4
|View full text |Cite
|
Sign up to set email alerts
|

Dutch population structure across space, time and GWAS design

Abstract: Previous genetic studies have identified local population structure within the Netherlands; however their resolution is limited by use of unlinked markers and absence of external reference data. Here we apply advanced haplotype sharing methods (ChromoPainter/fineSTRUCTURE) to study fine-grained population genetic structure and demographic change across the Netherlands using genome-wide single nucleotide polymorphism data (1,626 individuals) with associated geography (1,422 individuals). We identify 40 haplotyp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This still leaves the question of exactly which frequency of variants (or length of IBD segments) to use. The structure in most studies exists on multiple time scales, even in relatively homogeneous populations ( Byrne et al, 2020 ). In such cases, sets of PCs derived from variants in different frequency bins, or from IBD segments of different lengths, may be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This still leaves the question of exactly which frequency of variants (or length of IBD segments) to use. The structure in most studies exists on multiple time scales, even in relatively homogeneous populations ( Byrne et al, 2020 ). In such cases, sets of PCs derived from variants in different frequency bins, or from IBD segments of different lengths, may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Large GWAS in relatively homogeneous populations, such as the UK Biobank (UKB) ( Bycroft et al, 2018 ), should alleviate many of these concerns. However, such populations still exhibit fine-scale population structure ( Leslie et al, 2015 ; Karakachoff et al, 2015 ; Kerminen et al, 2017 ; Haworth et al, 2019 ; Raveane et al, 2019 ; Bycroft et al, 2019 ; Byrne et al, 2020 ). The extent to which this fine structure impacts GWAS inference in practice is largely unknown, and it is not clear whether existing methods adequately correct for it.…”
Section: Introductionmentioning
confidence: 99%
“…SOURCEFIND is a software tool that works directly on the output of the haplotype-based methods ChromoPainter and FineSTRUCTURE[ 9 ]. It has been previously utilized to capture genetic ancestry within Europe [ 12 , 16 , 40 ] and in Latin America[ 18 ]. We have previously shown that ChromoPainter and FineSTRUCTURE work well in our target population[ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We next performed PCA with prcomp function in R base [ 29 ] with the sum of IBD pairwise lengths computed separately using IBD segments with 1–2 cM and 5–7 cM to gain insights on the temporal population structure. To approximate the expected age of the IBD segments in these two bins (1-2 cM; 5-7 cM), we applied the formula described previously by Byrne et al [ 41 ], assuming a generation time of 25 years. Although the length of IBD segments represents wide time distributions, these expected values are point estimates that can be used as a reference.…”
Section: Methodsmentioning
confidence: 99%